2019
DOI: 10.1002/jsfa.9752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic thawing on the water‐holding capacity, physicochemical properties and structure of frozen tuna (Thunnus tonggol) myofibrillar proteins

Abstract: BACKGROUND The effect of ultrasonic thawing (0, 160, 280, 400 W) on water‐holding capacity (WHC), physicochemical properties and structure of tuna myofibrillar proteins was investigated. RESULTS Thawing time was shown to decrease and thawing loss to increase significantly (P < 0.05) as power increased (160–400 W), whereas there was no significant difference (P > 0.05) in cooking loss. Changes in T2 relaxation time were investigated using low‐field nuclear magnetic resonance. Ultrasonic thawing could significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The microscopic observation was measured using a microscope (Nikon80i, Nikon Ltd, Japan) according to the method of Li et al. () with minor modifications. Fish fillets were cut into 10 × 10 × 10 mm 3 along the fibers and stored in a refrigerator at −20 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microscopic observation was measured using a microscope (Nikon80i, Nikon Ltd, Japan) according to the method of Li et al. () with minor modifications. Fish fillets were cut into 10 × 10 × 10 mm 3 along the fibers and stored in a refrigerator at −20 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the frozen fish should be thawed before further processing. There are different thawing methods in foods reported, such as air thawing, water thawing, refrigerator thawing (Zhang, Li, Diao, Kong, & Xia, ), microwave thawing (Phinney, Frelka, Wickramasinghe, & Heldman, ), ultrasonic thawing (Li, Sun, Ma, Cai, & Li, ), high‐voltage electric field thawing (Mousakhani‐Ganjeh, Hamdami, & Soltanizadeh, ), high‐pressure thawing (Backi, ), and so on. However, each thawing method has its own disadvantages, which can lead to drip loss, nutritional value loss, lipid and protein oxidation, and microbial reproduction (Duygu & Ümit, ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2E, two peaks (287 and 296 nm) and two troughs (284 and 293 nm) were observed. The absorption peak at 287 nm was related with the interaction of tryptophan (Typ) and tyrosine (Tyr) residues, while the peak at 296 nm was attributed to tryptophan (Trp) residue (Li et al, 2019). There was a significantly longer shift (red shift) at peak of 296 nm in all thawed samples compared with the FS, suggesting that the unfolding occurred in protein molecules after thawed treatments and some hydrophobic residues were exposed because the fillets were oxidized, resulting in the increase in surface hydrophobicity.…”
Section: Raman Spectramentioning
confidence: 99%
“…Zhang, Cao, Cao, & Li, 2019). Li, Sun, Ma, Cai, and Li (2019) reported that there is a positive effect on water-holding capacity and microstructure of tuna fish by ultrasound thawing under 280 W power. Compared with the traditional thawing methods, far-infrared technology has the advantages of low cost and high product quality, and is widely used in food heating (Sakai & Hanzawa, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As it has been explained, the application of ultrasound would help to improve the transfer of energy due to the cavitation and the microstreaming generated in the liquid [96]. Some studies have been carried out in beef, pork, and codfish [102]; pork Longissimus dorsi muscle [103]; and tuna [104]. In a study carried out by Gambuteanu and Alexe [103], thawing assisted by ultrasound in samples of pork Longissimus dorsi muscle was evaluated.…”
Section: Thawingmentioning
confidence: 99%